Striking a Balance: Navigating Exemptions in Extradition for Terrorism and Political Offenses under International Law - Adnan, Sheikh Muhammad; Raza, Mohsin; Shahzad, Amir; Shahzad, Salman; Jameel, Raheel (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
This legal study critically analyzes the complexities of navigating exceptions to extradition, particularly concerning Terrorism and political offenses. It also distinguishes between comprehensive and sectoral conventions as well as universal and regional treaties, explaining the various approaches and their implications. It is a complex landscape of legal responses to international Terrorism. The efficacy of global conventions in addressing this very important issue is questionable. Each country has criteria for ascertaining what constitutes Terrorism and political offenses that can affect extradition. There is very little difference in the character of Terrorism and political offenses. Given the increasing global anxiety surrounding Terrorism and political offenses, this provides a significant perspective on the ongoing discourse on extradition in international law. This study uses a comprehensive qualitative methodology. It carefully examines legal texts, case law, and scholarly literature alongside a comparative analysis of extradition treaties and state practice. It used theories of democracy and Terrorism itself (which, in a global sense, must be fought) to distinguish and strike a balance between Terrorism and political offenses. Ultimately, this study has identified effective solutions to combat international Terrorism while addressing the differences between conventions. It also found a growing relationship between democratization and the global fight against Terrorism, with arguments for not categorizing acts of Terrorism as political offenses, especially in democracies. In addition, this study enhanced the understanding of the legal framework for countering international Terrorism and provided insight into the challenges and opportunities presented by various conventions. These findings have significant implications for refining extradition law, encouraging a balance that respects human rights, guarantees justice, prevents the abuse of the extradition process for political purposes, and contributes to the evolution of a fair and just international legal framework.